KONSEP KEBAHAGIAAN MENURUT AL-GHAZALI DALAM KIMIYA AS-SA’ADAH DAN RELEVANSINYA TERHADAP RUMAH TANGGA (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2021)
In the course of the household not all can feel happiness. Of course there are several factors that result in households not being able to achieve happiness, the cause of unhappiness may be due to economic factors, incompatibility between partners, not having children, infidelity and others. This study aims to see the concept of happiness according to Al-Gazali in his Kimiya As-Sa'adah. This type of research is library research. The primary data source is the translation of the Book of Kimiya as-Sa'adah and the secondary sources are books, internet and journals and other writings. Using the descriptive analysis method, namely paying attention to the concept of happiness in kimiya as-sa'adah by Imam al-Gazali by making it relevant to the household. The conclusion obtained from the results of this study is that Al-Gazali said that marriage that forms a household is one method of achieving happiness. The method in achieving happiness according to Al-Gazali can certainly be a solution to the existence of unhappiness in the first household: 1. Knowing yourself. 2. Knowing Allah, 3. Knowing the World, 4. Knowing the Hereafter, 5. Spirituality in Music, 6. Meditation and Remembrance, 7. Marriage, 8. Love of Allah.